Античный водопровод на хоре Нимфея - Зинько, В.Н. (Материалы по археологии, истории и этнографии Таврии, 2001)
Гидротехнические сооружения являлись важной составляющей древнегреческой урбанистической культуры. Условно эти сооружения можно разделить на несколько групп: 1) источники (колодцы, родники, фонтаны); 2) водосборные сооружения (водохранилища, цистерны); 3) водоводные системы (водопроводы, водостоки). Исследования боспорского города Нимфея (само название говорит о многом) выявили немало материалов по этой тематике. Hydro-technical constructions were a main component of Ancient Greek urban culture. However, this theme for Bosphoros cities has not been specifically researched yet. That is why the ancient water-supply found in the Chora of Nymphaion in 1997 is of such a great importance. A part of the water-supply was excavated at the distance of 2 kms from the city; it consisted of a well and a pipe-line. The inspection well was of a rectangular form. There was a square limestone trough on its bottom. Ceramic water-pipes were partially put into mainland loamy soil and were covered with flat pieces of limestone. In the process of excavation some fragments of Herakleion and Kios amphorae of the 4th century BC were found.